Acmeological conditions of harmonization of logical and emotional spheres of formation of professional skill of teachers of art disciplines (Pedagogy of Higher and Secondary Education, 2011)
In article conditions of harmonization of the logic and emotional parties of process of preparation of the future teachers of art disciplines  are aonsidered. Are analysed axemological conditions of this process, ways of formation of professional skill of the future teachers of music are certain.